Lexical-Structural Analysis of Phytonyms in Arabic (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article presents a lexical-structural analysis of phytonyms in the Arabic language. Phytonyms are terms denoting plant names, which are one of the most important lexical elements of the language. The article analyzes the full semantic content of phytonyms in the Arabic language, their structural structure, and the processes of formation of plant names. The article also examines various lexical, semantic, and grammatical features of phytonyms in the Arabic language. This study is of great importance in understanding the linguistic and semantic processes occurring in the context of phytonyms in the Arabic language.